Enhancing Existing Communication Services with Context Awareness - Bachir Chihani; Emmanuel Bertin; Irsalina Salsabila Suprapto; Julien Zimmermann; Noël Crespi (Journal of Computer Networks and Communications)
Context aware communication services rely on information sources and sensors, to derive users’ current situation and potential needs, and to adapt their communication services accordingly. If extensive studies have been driven on context awareness by industrials and researchers from academia, the design of such systems without modifying uses and manners of underlying communication services—while keeping them simple, intuitive, and reactive—remains a challenge. In this work, we introduce a context aware communication system that takes into account user’s preferences, workload, and situation to customize telephony services. In this implementation, we use IMS for communication management. The benefits of this implementation are the enhancement of IMS with context awareness features, and the coupling of user preferences with contextual information to provide improved service customization, without modifying the user experience.